Towards decentralized and sustainable water and wastewater treatment systems - Changsoo Lee; Lian-Shin Lin; Carlos A. Martínez-Huitle; Erica Pensini (Scientific Reports)
Abstract Achieving "sustainable management of water and sanitation for all" is a fundamental part of the Sustainable Development Goals (SDGs). Rising rates of urbanization and industrialization necessitate continual technological advancements to address existing and emerging water pollution issues related to centralized populations and industrial wastes. The articles in the Collection “Water and Wastewater Treatment Technologies” showcase salient aspects of advances in measurement and monitoring, as well as recommendations for sustainable use and management of water resources. The Collection associated with this editorial also presents studies that highlight the importance of decentralization and digitalization of environmental water technologies.